A gestão compartilhada nos colégios cívico-militares do Distrito Federal - Barreto, Jurenice da Silva (2021)
The object of this study is “Shared Management in Civic-Military Schools in the Federal District”. This investigation is part of the Research Line: “Policy, Management and Evaluation of Education”. The research problem is: What are the main challenges and possibilities in achieving the goals established in the Ordinance for the Implementation of Shared Management in Civic-Military Schools in DF? The period delimited for the study was between 2019 and 2021 (Shared Management in the DF started in 2019). The general objective of the research is to analyze the main challenges and possibilities in fulfilling the goals established in the Ordinance for Implementation of Shared Management in Civic-Military Schools in the Federal District. The specific objectives are: Contextualize the types of Management used in Basic Education Schools; Examine the CCMDF normative documents and their consonance with the Basic Education legislation; and Identify the main challenges and possibilities of shared management in CCMDF. The research adopted a qualitative approach, with exploratory and descriptive characterization. The methodological procedures were carried out through bibliographical, documental and empirical research. In the bibliographical research, there is a contextualization of the types of management used in Basic Education Schools - focusing on the essence of the CCM: shared management, discipline/hierarchy and meritocracy. We also searched for the main related works that have been produced so far, available on the Brazilian Thesis and Dissertation Library (BDTD), Scielo and Academic Google platforms. The documental research allowed the examination of the normative documents of the Civic-Military Schools in the Federal District and its consonance with the Basic Education Legislation: The 1998 Federal Constitution (CF), the National Education Guidelines and Bases Law (LDBEN) nº 9394 of 1996, the Child and Adolescent Statute (ECA), of 1990, the National Curriculum Guidelines (DCNs) of 2013 and 2015 and the National Curriculum Base (BNCC) of 2017. The empirical research had a data generation instrument online questionnaire, via Google Forms. The participants were students, teachers, managers and parents/guardians. The locus of the research was one of the Schools that are part of the Shared Management Schools Project of the Federal District. The data were analyzed in light of the fundamentals of several authors, such as Lima (2018), Sarkis (2019), Thums (2020), Silva (2007), among others. It is concluded, in a final analysis, that there are still challenges to be overcome by Shared Management, such as the resistance of most students regarding the established rules. However, some of the main objectives of the Joint Ordinance of Civic-Military School are being achieved, such as the reduction of violence within the researched School, the increase in discipline, the reduction of crime in the School and greater awareness of civic values, providing exercise of citizenship.